The sound and the furry [large type] : a Chet and Bernie mystery - Quinn, Spencer (Quinn, Spencer. Chet and Bernie mystery., 2014)
When Chet and Bernie happen upon a prison work crew that includes Frenchie Boutette, an old criminal pal they sent up the river, getting a new case is the last thing they expect. But Frenchie, who comes from an old Louisiana family full of black sheep, needs help finding his one law-abiding relative, his brother Ralph, a reclusive inventor who has gone missing with his houseboat. At first it seems as if Ralph's disappearance is connected to a dispute over a load of stolen shrimp. But the investigation heads in a dangerous new direction involving the oil business and an impending environmental catastrophe.